Professional search engine optimization with PHP a developer's guide to SEO - Sirovich, Jaimie 1981-; Darie, Cristian (Wiley Technology Pub., 2007)
Maybe you're a great programmer or IT professional, but marketing isn't your thing. Or perhaps you're a tech-savvy search engine marketer who wants a peek under the hood of a search engine optimized web site. Search engine marketing is a field where technology and marketing are both critical and interdependent, because small changes in the implementation of a web site can make you or break you in search engine rankings. Furthermore, the fusion of technology and marketing know-how can create web site features that attract more visitors. The mission of this book is to help web developers create web sites that rank well with the major search engines, and to teach search engine marketers how to use technology to their advantage. We assert that neither marketing nor IT can exist in a vacuum, and it is essential that they not see themselves as opposing forces in an organization. They must work together. This book aims to educate both sides in that regard.
Keywords: PHP (Computer program language); Web sites -- Design; Search engines; Search Engine; PHP (Langage de programmation); Sites Web; Conception; Moteurs de recherche; search engines; Web sites; Design